New liquid chromatography assays for simultaneous quantification of antihypertensives atenolol and valsartan in their dosage forms - Peleshok, K.; Piponski, M.; Kovalenko, S.; Ahmed, H.; Abdel-Megied, A.; Ezike, O. F.; Logoyda, L.; Коваленко, Сергій Іванович (My University, 2021)
Nowadays, various single-pill combinations are used as the best choice in hypertension management. However, these pills made a high challenge to analysts in terms of quality control assays. We have developed three sensitive, selective, fast, simple, green, accurate, precise, and robust isocratic high-performance liquid chromatography methods for simultaneous determination of valsartan and atenolol in dosage forms. To find the appropriate high-performance liquid chromatography conditions for the separation of the examined drugs, various columns, isocratic mobile phase systems were tried, and successful attempts were performed. The used columns proved to be indispensably applicable and gave a shorter analysis time and peak symmetries. This reduction in total run time leads to low solvent consumption and makes all methods more economical. The linearity, accuracy, and precision remained within the acceptable limits. Therefore, all developed methods are suitable for the routine quality control analysis of any pharmaceutical preparation containing the two tested drugs with the proposed chromatographic methods advantages for checking quality during stability studies of their pharmaceutical preparations.
Keywords: Atenolo; liquid chromatography; single-pill combinations; valsartan